PENGARUH GREEN ADVERTISING DAN GREEN CLAIM PADA NIAT MEMBELI ULANG KONSUMEN GREEN PRODUCT - Priyantika, Agung Ari; Wardana, I Made (E-Jurnal Manajemen, 2015)
ABSTRACT Green product is a product that started emerging due to environmental issues and problems that occur at this time, Environmental issue is connected with green product.. Green product is also connected with green advertising and green claim. This study aimed to analyze the effect of green advertising and green claims on repurchase intention of consumer of the green products (bottled water products AQUA). By using purposive sampling, the samples taken as many as 100 people. Data collected by using a questionnaire. Based on the results of the analysis showed green and green advertising claims positive effect on repurchase intention green product. It is proved that the product claims in advertising in accordance with the wishes of consumers can affect consumer intention to buy again. Keywords: green advertising, green claims, repurchase intention
Keywords: green advertising; green claim; repurchase intention